2017
DOI: 10.1177/0886260517736879
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Home Visiting Program on Parenting: Mediating Role of Intimate Partner Violence

Abstract: Young women aged 18 to 24 years are in the highest risk group for intimate partner violence (IPV), and adolescent mothers are at particularly high risk for IPV and for risky health behaviors. Exposure to IPV may contribute to parenting stress and risky behaviors, and may compromise parenting behavior and healthy child development. The present study examined whether program effects of a statewide home visiting program for adolescent parents on young mothers' parenting stress and risky behaviors measured 2 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Home visiting is also looked to as a strategy to address postpartum mental health challenges, though impact studies have produced disappointing results overall (e.g., Ammerman et al, 2019; Leonard et al, 2020). In addition, despite routine screening for household risks such as intimate partner violence and substance use, evidence of home visiting impact on these outcomes is mixed (Duggan et al, 2004; Easterbrooks et al, 2021; Kitzman et al, 2019). Modifying the curricular focus of home visiting programs could increase their impact in these domains and, in turn, their effectiveness in promoting child development.…”
Section: Discussionmentioning
confidence: 99%
“…Home visiting is also looked to as a strategy to address postpartum mental health challenges, though impact studies have produced disappointing results overall (e.g., Ammerman et al, 2019; Leonard et al, 2020). In addition, despite routine screening for household risks such as intimate partner violence and substance use, evidence of home visiting impact on these outcomes is mixed (Duggan et al, 2004; Easterbrooks et al, 2021; Kitzman et al, 2019). Modifying the curricular focus of home visiting programs could increase their impact in these domains and, in turn, their effectiveness in promoting child development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the prevalence of IPV is associated with an increase in depression in both genders, as well as the substance abuse, anti-social behaviors, and suicide in girls and the high levels of high-risk behaviors in both genders (72). IPV also causes high-risk behaviors in adolescent mothers (73). According to the study by Gage, 8% of 15-year-old versus 2.5% of 24-year-old married adolescents had suicide thoughts and attempts (74).…”
Section: Mental Healthmentioning
confidence: 99%
“…Other research has considered the effects of specific programs targeted at victims of IPV. Easterbrooks and colleagues [ 33 ] used longitudinal data from a sample of U.S. young mothers and demonstrated that the effects of a home visiting program on maternal well-being (both parenting stress and risky behaviors) two years after program enrollment were mediated by reductions in IPV one year earlier. Another study assessed the outcomes of the Nurse–Family Partnership program for pregnant women [ 34 ].…”
Section: Introductionmentioning
confidence: 99%